The Effect of Audit Quality and Financial Conditions on Audit Opinion (Study on Food and Beverage Manufacturing Companies Listed on The Indonesia Stock Exchange) - Dwi Kartika Sari (Publikasi Indonesia, 2021)
This research was conducted to determine how to influence the quality of auditing and financial condition of the going concern audit opinion on the company Food and Beverages which is listed on the Stock Exchange in 2010-2014. The method used in this research is descriptive and verification. A descriptive study serves to illustrate the characteristics of a population. While research verification is used to reexamine the results of previous studies with this gracious purpose correctness of the results of previous studies. The population in this study amounted to 22 companies Food and Beverages in the study period from 2010 to 2014. Then the 10 companies in the sample were obtained by using the purposive sampling method of sample collection techniques with particular consideration. Data were obtained from the Indonesian Stock Exchange. Analysis of the data used in this research is the logistic regression analysis. Analysis of the study data processing using the software Microsoft Office Excel 2007 and SPSS for windows 20 o'clock. The coefficient of determination R2 shows that the variable quality of auditing and financial condition is explained by the independent variable by 3.8% and 96.2% influenced by other factors outside the model. The variable quality audit has no significant effect on the going concern audit opinion. And financial condition variables, not significant affect ongoing concern audit opinion.